Intrathyroidal Parathyroid Carcinoma: Report of an Unusual Case and Review of the Literature - Lizette Vila Duckworth; William E. Winter; Mikhail Vaysberg; César A. Moran; Samer Z. Al-Quran (Case Reports in Pathology)
Intrathyroidal parathyroid carcinoma is an exceedingly rare cause of primary hyperparathyroidism. A 51-year-old African American female presented with goiter, hyperparathyroidism, and symptomatic hypercalcemia. Sestamibi scan revealed diffuse activity within an enlarged thyroid gland with uptake in the right thyroid lobe suggestive of hyperfunctioning parathyroid tissue. The patient underwent thyroidectomy and parathyroidectomy. At exploration, a 2.0 cm nodule in the usual location of the right inferior parathyroid was sent for intraoperative frozen consultation, which revealed only ectopic thyroid tissue. No parathyroid glands were identified grossly on the external aspect of the thyroid. Interestingly, postoperative parathyroid hormone levels normalized after removal of the thyroid gland. Examination of the thyroidectomy specimen revealed a 1.4 cm parathyroid nodule located within the parenchyma of the right superior thyroid, with capsular and vascular invasion and local infiltration into surrounding thyroid tissue. We present only the eighth reported case of intrathyroidal parathyroid carcinoma and review the literature.